Stepwise approach to establishing multiple outreach laboratory information system-electronic medical record interfaces - Liron Pantanowitz; Wayne LaBranche; William Lareau (Elsevier, 2010)
Clinical laboratory outreach business is changing as more physician practices adopt an electronic medical record (EMR). Physician connectivity with the laboratory information system (LIS) is consequently becoming more important. However, there are no reports available to assist the informatician with establishing and maintaining outreach LIS-EMR connectivity. A four-stage scheme is presented that was successfully employed to establish unidirectional and bidirectional interfaces with multiple physician EMRs. This approach involves planning (step 1), followed by interface building (step 2) with subsequent testing (step 3), and finally ongoing maintenance (step 4). The role of organized project management, software as a service (SAAS), and alternate solutions for outreach connectivity are discussed.